Association between triglyceride-glucose index and its obesity indicators with hypertension in postmenopausal women: a cross-sectional study - Zhang, Bo; Jiang, Daoli; Ma, He; Liu, Huanxian (Frontiers in Nutrition, 2025)
BackgroundThis study explored the association between the triglyceride-glucose (TyG) index, combined with adiposity metrics, and hypertension prevalence in postmenopausal women.MethodsA cross-sectional study was conducted using data from 4,302 postmenopausal women in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. Multivariable adjusted logistic regression models and restricted cubic splines (RCS) were implemented to assess the dose-response relationship. Receiver operating characteristic (ROC) curves were employed to compare the diagnostic performance of the TyG index, TyG-body mass (TyG-BMI), TyG-waist circumference (TyG-WC), and TyG-waist-to-height ratio (TyG-WHtR).ResultsMultivariable-adjusted analyses demonstrated that the TyG index and its obesity indicators are significantly associated with hypertension risk. The RCS curve exhibited a non-linear relationship between TyG-WHtR and hypertension (P for non-linearity = 0.026), whereas other indices showed linear associations. ROC analysis confirmed the superior discriminative ability of TyG-WHtR for hypertension (AUC = 0.643, 95% CI 0.625–0.660).ConclusionThe TyG index and its combined obesity indicators, particularly TyG-WHtR, are strongly associated with hypertension risk in postmenopausal women. TyG-WHtR may serve as a valuable biomarker for targeted screening in this population.